EVALUATION OF REFILLABLE DRINKING WATER QUALITY BASED ON MPN COLIFORM AND ESCHERICHIA COLI IN SESETAN VILLAGE, SOUTH DENPASAR, BALI - Wyasena, Pande Nyoman Tri Saguna; Sudaryati, Ni Luh Gede; Sudiartawan, I Putu; Adnyana, I Made Dwi Mertha (Journal of Vocational Health Studies, 2022)
Background: Refilled drinking water given by depots that currently have a permit for operation can be used to meet the community's drinking water demands. However, the quality of refilled drinking water has been tainted with pathogens that can cause health problems. Purpose: To assess the quality of replenished drinking water in Sesetan Village using Most Probable Number (MPN) Coliform and Escherichia coli as indicators. Method: A qualitative approach to descriptive observational research. The Ministry of Health standard 492/Menkes/PER/IV/2010 is used to assess drinking water quality. In this investigation, ten samples were used. Sampling was conducted in Sesetan Village, South Denpasar, Bali. Result: MPN Coliform was found in four samples: 96 MPN/100 mL (X1), 38 MPN/100 mL (X7), 15 MPN/100 mL (X8), and 5 MPN/100 mL (X10). Meanwhile, all of the samples tested negative for Escherichia coli. Conclusion: Based on drinking water quality criteria, 4 (40%) refilled drinking water depots (DAMIU) did not meet quality requirements (Ministry of Health Regulation number 492/Menkes/PER/2010).